2006
DOI: 10.1136/pgmj.2005.044594
|View full text |Cite
|
Sign up to set email alerts
|

Hip resurfacing: a technology reborn

Abstract: In recent years there has been a resurgence of interest in the concept of hip resurfacing. Much of this interest has stemmed from the work of McMinn in the West Midlands. Hip resurfacing is now emerging as a viable alternative to conventional hip replacement. In this article, we discuss the conceptual advantages offered by hip resurfacing and review the early clinical results and the ongoing clinical concerns regarding this technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…As patients receiving THA are increasingly (biologically) younger and active, the development of less invasive approaches and bone preserving solutions has been a key focus during the last decade [8,9]. HR has emerged as a promising way of sparing bone, while retaining the biomechanics of the hip joint and potentially allowing a facilitated revision, if necessary [10,11]. However, concerns about wear and longevity have arisen in the process [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…As patients receiving THA are increasingly (biologically) younger and active, the development of less invasive approaches and bone preserving solutions has been a key focus during the last decade [8,9]. HR has emerged as a promising way of sparing bone, while retaining the biomechanics of the hip joint and potentially allowing a facilitated revision, if necessary [10,11]. However, concerns about wear and longevity have arisen in the process [12,13].…”
Section: Introductionmentioning
confidence: 99%
“… 14 Various studies have shown that functional utility of THA reduces to 80% at 10 years, 33% at 16 years, subsequently requiring a revision surgery. Alternate bearing surfaces like metal on metal or ceramic on ceramic decrease the wear rate but have their own set of complications (metallosis, squeaking) 32 33 34 35 36 37 38 39 and long term results are still awaited. 40 When compared with BHA, conflicting results have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The BHR device led the resurgence of interest in MoM hip replacements after being introduced by Midlands Medical Technology in 1997. 13 The BHR is a highly polished, dual radius MoM bearing couple which is said to promote ideal joint lubrication resulting in very low wear rates. 14 This device was buoyed by several successful early short-term studies and became immensely popular in the UK.…”
Section: Mom Devices and Regulationmentioning
confidence: 99%